ATTENUATION OF SEISMIC WAVES IN THE LITHOSPHERE OF THE NORTHERN PART OF THE BASIN AND RANGE PROVINCE - А. А. Dobrynina (Геодинамика и тектонофизика)
This paper presents results of the study of attenuation of seismic waves in the lithosphere and upper mantle of the northern part of the Basin and Range Province (BRP) (Fig. 1). In this study, the coda-wave method [Aki, Chouet, 1975] is applied to process data collected in the seismic experiment conducted in 1988–1989, PASSCAL Basin and Range Passive Seismic Experiment [Owens, Randall, 1989], including records of 66 earthquakes and explosions (Mb=1.1–5.0) which occurred in BRP (Fig. 2).The effective seismic quality factor by the coda is calculated using the single-backscattering model [Aki, Chouet, 1975]. The QC values are calculated for 18 values of the lapse time window W from 10 to 95 sec with the step of 5 sec at six (6) central frequencies (0.3, 0.75, 1.5, 3.0, 6.0, and 12.0 Hz). In total, 7776 individual measurements of QC were done. It is observed that the quality factor QC is strongly dependent on the frequency and the lapse time window W: QC increases from 12±6 to 359±17 for the central frequencies of 0.3 and 12.0 Hz when the lapse time window is W=10 sec and from 87±6 to 1177±87 for the same frequencies when W=95 sec (Fig. 6). On the basis of the QС values obtained for all the lapse time windows W empirical relationships of quality factors and frequencies are calculated according to [Mitchell, 1981], and values of quality factor Q0 at reference frequency f0 (f0=1 Hz) and frequency parameter n (which is close to 1 and varies depending on the heterogeneity of the medium [Aki, 1981]) are obtained. In this study, Q0 varies from 60±8 to 222±17, the frequency parameter ranges from 0.57±0.04 to 0.84±0.05, and the attenuation coefficient δ varies from 0.015 to 0.004 km–1, depending on W (Fig. 8); similar values of attenuation parameters are typical of regions with high tectonic activity [Mak et al., 2004].In the single-backscattering model, the dependence of the attenuation parameters from the lapse time window can be explained in terms of the depth of formation of the coda [Pulli, 1984]: a larger value of W corresponds to a greater depth through which the coda-waves go. As shown by the analysis of variations of attenuation coefficient δ and frequency parameter n for the Basin and Range Province, both parameters decrease irregularly with depth – the slope of the curve showing variations of δ is considerably changed at the depth of 150 km. At the top of the graph (to the depth of 150 km), an abrupt change of δ with depth is observed; it is clearly seen in the graph of gradient δ (Fig. 9 and Fig. 10); such behaviour is also characteristic of n. At the depth of 140 km, parameter n is increased. In the middle section (at depths of 150–200 km), the slope of the δ curve increases, and gradients of δ and the frequency parameter are significantly reduced. At the bottom of the profile (> 200 km), the value of δ is almost constant, and an abrupt increase of n is observed (Fig. 9 and Fig. 10). Figure 10 shows the high-speed profile of the area under study, which is published in [Wagner et al., 2012]. The profile shows the low velocity mantle under the Basin and Range Province, actually starting underneath the Moho (at the depth of 50–60 km). The lower boundary of the low-velocity mantle is located at the depth of 130–160 km. Thus, there are grounds to conclude that the change in the slope of the curve showing dependence of δ from the depth is related to the deep structure of the medium. The abrupt changes of δ and n are associated with the velocity discontinuities of the medium. The high values of δ and n, which are characteristic of the upper part of the profile, indicate the high degree of heterogeneity of the medium, which is also confirmed by the low velocities of seismic waves in the area under study [Wagner et al., 2012]. The reduction of parameters  δ and n in the middle and lower parts of the profile suggests a more homogeneous structure of the medium at largerdepths.As a result of the study of the characteristics of seismic wave’s attenuation in the lithosphere and the upper mantle of the northern part of the Basin and Range Province, it is established that the effective seismic quality factor QC is highly dependent on the frequency in the range of 0.5–16.0 Hz. The empirical relationships of Q(f) for various lapse time windows are obtained; it is shown that increasing the lapse time window causes the values of the effective seismic quality factor to increase, which may be interpreted as reduction of attenuation with depth. By comparing the depth variations of the attenuation coefficient and the frequency parameter against the velocity structure, it is shown that there is a distinct change in attenuation of seismic waves at the velocity discontinuities in the northern part of the Basin and Range Province.